2005
DOI: 10.1111/j.1469-0691.2004.01036.x
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of linezolid resistance in Germany, 2001–2002

Abstract: A surveillance study was performed throughout Germany from November 2001 to June 2002 to assess the prevalence of linezolid-resistant isolates among Gram-positive bacteria from routine susceptibility data and to compare the in-vitro activity of linezolid to that of other antibacterial agents. Each of 86 laboratories provided routine susceptibility data for 100 consecutive isolates. Most laboratories (c. 60%) used the disk diffusion test. Laboratories were also requested to send a representative sample of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…[17][18][19][20][21] Despite increased linezolid usage, international surveillance data still show a relatively low incidence of linezolid-resistant Enterococcus, with a prevalence rate of 2% or less, and reports of linezolid-resistant VRE are limited to case reports and institutional outbreaks. [1][2][3][4][5][6][11][12][20][21][22][23] However, in our hospital, microbiological data showed a much higher prevalence of linezolid resistance among Enterococcus isolates, at 9.8%, and in this study we found the prevalence of linezolid resistance among VRE isolates to be 20%. A potential explanation for this would be the much higher and continually increasing rate of linezolid usage at our institution, compared with the national average (17.4 vs 6.3 DDD per 1,000 patient-days).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…[17][18][19][20][21] Despite increased linezolid usage, international surveillance data still show a relatively low incidence of linezolid-resistant Enterococcus, with a prevalence rate of 2% or less, and reports of linezolid-resistant VRE are limited to case reports and institutional outbreaks. [1][2][3][4][5][6][11][12][20][21][22][23] However, in our hospital, microbiological data showed a much higher prevalence of linezolid resistance among Enterococcus isolates, at 9.8%, and in this study we found the prevalence of linezolid resistance among VRE isolates to be 20%. A potential explanation for this would be the much higher and continually increasing rate of linezolid usage at our institution, compared with the national average (17.4 vs 6.3 DDD per 1,000 patient-days).…”
Section: Discussionmentioning
confidence: 58%
“…Linezolid resistance in VRE, although relatively uncommon, was initially associated with prolonged exposure to linezolid. [1][2][3][4][5][6] However, more recently, linezolid-resistant VRE has been isolated from patients who did not have prior antimicrobial exposure, which is more consistent with horizontal transmission of the organism. 5,[7][8][9][10][11][12] Furthermore, newer data document a much higher prevalence of linezolid-resistant organisms-11% to 17%-recovered from patients colonized or infected with VRE.…”
mentioning
confidence: 99%
“…Epidemiologic studies indicate that the overall prevalence of linezolid resistant clinical S. aureus isolates is low [15]. So far, most linezolid resistant S. aureus emerged during prolonged therapy with linezolid [7,10,11].…”
mentioning
confidence: 99%
“…Furthermore, levofloxacin and vancomycin (82), vancomycin and cefpirome (84), vancomycin (85), and various fluoroquinolones (86) reduce viable counts of S. epidermidis and CoNS, respectively, less effectively than those of S. aureus. Likewise, oral streptococci are almost always less susceptible than or at least as susceptible as S. pneumoniae to the agents studied (74,(87)(88)(89)(90)(91).…”
Section: Pd Effects On the Human Resident Microflora As A Model Of A mentioning
confidence: 99%